Outcomes and management of type A intramural hematoma - Sandhu, Harleen K.; Tanaka, Akiko; Charlton-Ouw, Kristofer M.; Afifi, Rana O.; Miller III, Charles C.; Safi, Hazim J.; Estrera, Anthony L. (Annals of Cardiothoracic Surgery, 2016)
Background: Initial optimal management of acute type A aortic dissection (ATAAD) with intramural hematoma (ATAIMH) remains controversial, especially between centers in the Eastern vs. Western worlds. We examined the literature and our experience to report outcomes after repair of ATAIMH. Methods: We reviewed the hospital, follow-up clinic records and online mortality databases for all patients who presented to our center for open repair of ATAAD between 1999 and 2014. Preoperative characteristics, early and long-term outcomes were compared between classic ATAAD vs. ATAIMH. Survival was analyzed using Kaplan-Meier and log-rank statistics. Results: Of the 523 repaired ATAAD, 101 patients (19%) presented with IMH and 422 (81%) had classic dissection. ATAIMH were significantly older (64.8±12.9 vs. 56.8±14.6 years; P